2010
DOI: 10.2754/avb201079010073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Humate on the Content of Trace Elements in Organs of Weaned Piglets

Abstract: The purpose of the present study was to assess the effect of a 21-day feeding of a diet with 1% inclusion of sodium humate (HNa) on the content of trace elements (copper, zinc, selenium, manganese, cobalt) in tissues of weaned piglets, their efficiency and biochemical indicators. Significantly lower content of manganese in livers (P < 0.01) and kidneys (P < 0.05) was detected in piglets fed the 1% HNa supplemented diet in comparison with control, non-treated animals. The concentrations of selenium in blood ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Although HSs can combine with metal ions, oxides and clay to form water-soluble or insoluble complexes and can interact with organic compounds (Boyd et al, 1981;Livens, 1991;Islam et al, 2005), only a few studies have investigated the specific effects of FA or HA on the intestinal absorption of trace elements (Willis, 2015) and on the trace element concentrations in different organs of piglets (Zraly and Pisarikova, 2010) and rats (Cagin et al, 2016).…”
mentioning
confidence: 99%
“…Although HSs can combine with metal ions, oxides and clay to form water-soluble or insoluble complexes and can interact with organic compounds (Boyd et al, 1981;Livens, 1991;Islam et al, 2005), only a few studies have investigated the specific effects of FA or HA on the intestinal absorption of trace elements (Willis, 2015) and on the trace element concentrations in different organs of piglets (Zraly and Pisarikova, 2010) and rats (Cagin et al, 2016).…”
mentioning
confidence: 99%
“…Increased concentrations of blood serum glucose, triacylglycerols (P < 0.01), calcium and iron (P < 0.05) were detected in experimental vs. control piglets. The results of the present study indicated that despite a positive effect, sodium humate caused a decrease in concentration of physiologically important manganese and selenium in the tissues [12].…”
Section: Application Of Probiotic "Stimix Zoostim" In Calves Managementmentioning
confidence: 41%
“…We observed a tendency to increase the calcium content with age in young rabbits of the experimental and control groups. Several possible mechanisms of the effect of humic additive on calcium absorption have been described (Zralý et al, 2010;Trckova et al, 2018). Humic acid additives are known for their chelating properties, which are due to the presence of carboxyl and hydroxyl functional groups in them.…”
Section: Discussionmentioning
confidence: 99%
“…The literature includes statements about ambiguity of the effect of humic additive on the calcium content in the blood. A number of researchers have noted an increase in serum calcium in piglets when humic additive is added to their main diet (Zralý et al, 2010;Trckova et al, 2018). But an increase in the blood calcium was not observed in the studies of humic additive in rabbits and birds (Stepchenko et al, 1991;Mista et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation